Safe Use of Butorphanol–Azaperone–Medetomidine to Immobilize Free‐Ranging White‐tailed Deer. (2nd June 2020) - M Dermott, Joseph R.; Leuenberger, Wendy; Haymes, Caleb A.; Clevinger, Garrett B.; Trudeau, Jonathan K.; Carter, Tim C.; Hast, John T.; Jenkins, Gabriel S. W.; Bowling, Will E.; Cox, John J.
ABSTRACT: Butorphanol–Azaperone–Medetomidine (BAM) is a relatively new drug mixture compounded for the past decade to immobilize mammals, particularly ungulates. Despite its increased use in recent years, scant research has quantified the physiologic responses of immobilized animals or assessed its relative efficacy using different trapping methods. We tested the safety and efficacy of BAM for use in the immobilization of 198 free‐ranging white‐tailed deer ( Odocoileus virginianus ) captured using drop‐nets, Clover traps, and gun‐propelled darts from 1 January 2014 to 28 July 2016 in Kentucky and Indiana, USA. Use of BAM produced a safe and satisfactory plane of immobilization that rarely required treatment of side effects. First signs of induction were observed on average at 4.4 ± 0.2 (standard error) minutes post–intramuscular administration, and deer reached lateral recumbency at 8.6 ± 0.4 minutes. Times to first signs of induction and the induction period were longer for adults than for juveniles, while times to the first sign of reversal, lifting head, and standing were longer for juveniles than adults. Although physiologic responses of deer during induction were within published norms, respiration rates, body temperature, heart rates, and oxygen saturation typically declined throughout the immobilization period. Our BAM dose did not affect time to recovery or heart rate. Regardless of trapping method, on average, heart rate was 61.2 ± 0.7 beats/minute, respiratory rate was 29.1 ± 0.5 breaths/minute, temperature was 38.93° ± 0.04° C, and oxygen saturation was 85.0% ± 0.3%. Deer showed first signs of reversal at 4.3 ± 0.3 minutes after administration of the reversal agent intramuscularly or half‐intramuscularly and half‐intravenously and were fully recovered after 6.3 ± 0.4 minutes. In summary, we found that BAM was an efficacious and safe drug to use on white‐tailed deer captured by a variety of trapping methods. © 2020 The Wildlife Society. Abstract : We tested the safety and efficacy of Butorphanol–Azaperone–Medetomidine (BAM) for use in the immobilization of free‐ranging white‐tailed deer captured using drop‐nets, Clover traps, and gun‐propelled darts in Kentucky and Indiana, USA. Administration of BAM‐induced anesthesia quickly, maintained a safe plane of anesthesia and acceptable physiological parameters, and was rapidly reversed, making this drug a safe and reliable alternative to other potentially dangerous or inefficacious drugs or combinations.